The Teaching Quality of Teachers in a Learning Process - Susanti, Susanti; Harapan, Edi; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2022)
This study attempts to describe the teaching quality of teachers in learning in SD Negeri 24 Banyuasin III. The qualitative was used in this study. Informants in research were head of school and teachers. The data collection in this study using interviews. The results suggests that the quality of teachers faced lack of facility system, lack of funds, then it needs strategy to maximize resources which will run the learning well and the achievement of students gained.